Effects of Seismic Lines on the Abundance of Breeding Birds in the Kendall Island Bird Sanctuary, Northwest Territories, Canada - Ashenhurst, Amber R.; Hannon, Susan J. (ARCTIC, 2009)
Current plans to increase oil and gas exploration and extraction in the Canadian Arctic include development in the Kendall Island Bird Sanctuary, Northwest Territories. Various studies have shown impacts of seismic lines on vegetation, but the effects on bird abundance in the Arctic are poorly known. We evaluated the impact of new (0.5–1.5 years old) and old (10–35 years old) visible seismic lines within the sanctuary on the abundance of breeding passerines (savannah sparrow, Passerculus sandwichensis; Lapland longspur, Calcarius lapponicus; common redpoll, Carduelis flammea; American tree sparrow, Spizella arborea; and red-necked phalarope, Phalaropus lobatus) in upland tundra, low-centre polygon, and sedge/willow habitats. Along new seismic lines, effects on abundance were not statistically significant for most groups of birds, although the trend in most habitats was for more birds on reference transects than on seismic lines. Significant impacts were found for passerines grouped in upland tundra and for savannah sparrow in sedge/willow. The latter effect (possibly due to standing water along the line) was not significant the following year. Along old seismic lines, abundance of passerines was lower than on reference transects in upland tundra and low-centre polygon habitat, except for Lapland longspurs in upland tundra. Lines created 10–30 years ago have persistent vegetative changes and this appears to have reduced bird abundance. Although we did not plot individual territories, birds were seen crossing the seismic lines and sometimes perched on them, suggesting that they were not avoiding the lines altogether. Instead, these birds may have increased territory size to compensate for vegetative changes along the lines. Les plans actuels visant l’intensification des travaux d’exploration et d’extraction pétrolière et gazière dans l’Arctique canadien visent la mise en valeur du refuge d’oiseaux de l’île Kendall, dans les Territoires du Nord-Ouest. Même si diverses études ont permis de démontrer les effets des ...